If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 7 + -2x Solving 9 = 7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 2x = 7 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 2x = 7 + 0 9 + 2x = 7 Add '-9' to each side of the equation. 9 + -9 + 2x = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 7 + -9 2x = 7 + -9 Combine like terms: 7 + -9 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| -2+5x=16+8 | | 6x^4+6x-42=0 | | -6(2x-2)=-12x+12 | | 61=3v+10 | | 10x-8y-9z=0 | | 0.50(2x-6)=4(x-1) | | 21+6x=y | | 51=3.50p+5.50+6 | | x^2-50x+25=0 | | 2x+4y+3z=3 | | 21x^2y-15xy^2+9x^2y^2= | | -6n-(8n-5)=14-n | | x^2-6x=x(3+x) | | -6n-(8n-5)=14-2 | | w+13=10 | | d+9=35 | | a^2-48=0 | | 2x+10=8x+40 | | 7=y+6 | | 3x^2+2x+8=112 | | -15=-2+4m+7 | | -15=-2+4m+7 | | 8x-3=-2+4x | | Q+6=rt+2 | | -15=-2+4m+7 | | -9-5n=-44 | | 2x*5y=16 | | -4(8)-9=-23 | | 12-6x=2-4x | | 17.50+3.50x=125 | | -2=k+6-3k | | -36-(2x-21.6)+13.4x= |